Radar imaging with EISCAT 3D - J. Stamm; J. Vierinen; J. M. Urco; B. Gustavsson; J. L. Chau (Annales Geophysicae, 2021)
A new incoherent scatter radar called EISCAT 3D is being constructed in northern Scandinavia. It will have the capability to produce volumetric images of ionospheric plasma parameters using aperture synthesis radar imaging. This study uses the current design of EISCAT 3D to explore the theoretical radar imaging performance when imaging electron density in the E region and compares numerical techniques that could be used in practice. Of all imaging algorithms surveyed, the singular value decomposition with regularization gave the best results and was also found to be the most computationally efficient. The estimated imaging performance indicates that the radar will be capable of detecting features down to approximately 90×90 m at a height of 100 km , which corresponds to a ≈0.05∘ <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="38pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="7b2ab9850ba1c59fd035d756f43deafe"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="angeo-39-119-2021-ie00001.svg" width="38pt" height="11pt" src="angeo-39-119-2021-ie00001.png"/></svg:svg> angular resolution. The temporal resolution is dependent on the signal-to-noise ratio and range resolution. The signal-to-noise ratio calculations indicate that high-resolution imaging of auroral precipitation is feasible. For example, with a range resolution of 1500 m , a time resolution of 10 s, and an electron density of 2×10<mn ...